IMPLEMENTASI KEBIJAKAN PROYEK OPERASI NASIONAL AGRARIA DI DESA BUKUMATITI KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - Baura, Yelmilanda; Rumapea, Patar; Rorong, Arie Junus (JURNAL ADMINISTRASI PUBLIK, 2016)
The problems at once which is the goal of this research is how the implementation of the National Agricultural Policy Operation Project (Prona) in the village of Bukumatiti, District Jailolo, West Halmahera. This study was used a qualitative approach aims to descriptive the meaning behind the reality, which takes place in the field. Informants in this study amounted to 13 respondents with key informants Village Head and BPD. The data collection technique was interview and observation. The data were analyzed using an interactive model of Miles and Huberman.The results of this study indicate that the communication factor has not been effective, human resources related to the performance of the village government of lesser quality, disposition or attitude of the village administration in running the program does not currently work well so that in practice there is a gap and the lack of timely, the next bureaucratic structure has not in accordance with the applicable rules resulting in less than optimal service process.Based on the research results suggested that the necessary cooperation from the National Land Agency (BPN) and the village government, in improving government performance and BPN village to implement a policy. Also required good communication from the village government in order to provide the right information related to the programs, so that the implementation of Prona can be realized properly and in accordance with the applicable rules.Keywords: Policy Implementation, Project National Agricultural Operations (Prona)